Fatty acid composition of Malaysian giant mudskipper (Periophthalmodon schlosseri) fish oil - Omar, Muhammad Nor; Che Othman, Siti Fairuz; Mohamad Talib, Hasan; Yunus, Kamaruzzaman (2010)
Background: The mudskipper (P. schlosseri) belongs to the Periophthalmin spp. within the family Gobiidae. They live in the mangrove swamps and intertidal habitats which are found only in tropical and subtropical regions. In some countries, the mudskipper provides a valuable source of protein throughout the Asian and African regions. Objective: The main aim of the present study is to look into the composition of the Malaysian giant mudskipper lipid which might be useful to human health by looking into the ratio of ω- fatty acids present in P. schlosseri oil. Procedures: The fish oil from Malaysian mudskipper fish was extracted using a modified Folch method. After methylation, the fish oil was analysed by GC and GC-MS. An HP-5 non-polar capillary column was used and the temperature was initially kept at 50oC for 2 min and then programmed at 5oC min-1 to 250oC. The injector and detector temperatures were 220o and 250oC respectively and He gas was used as carrier gas with a flow rate of 1.2 ml min-1. Result: The GC and GC-MS results showed that the major chemical constituents of P. schlosseri oil were palmitic (16:0) (23.0%) and stearic acid (C18:0) acid (29.2%), oleic acid (C18:1), (12.6%). The total saturated fatty acid (SFA) was also found to be high (48.3%). The ratio of the total saturated (SFA) and unsaturated acids (USFA) was 1:0.9 and it is considered that the giant snakehead fish oil is good for human consumption. Conclusion: The result shows that the total ω-6 content of P. chhlosseri was 15.4% and it has ω-3 and ω-6 ratio of 1:1.